EFFECTIVENESS OF FOREIGN LANGUAGE TEACHING AND PRIORITIES OF TRANSLATION TEACHING METHODS - Kurbonova Nargiza Samadovna; Jo’rayeva Shaxnoza Olimovna (Scholars Digest Publishing, 2023)
This article focuses on the development of translation skills along with the study of foreign languages, taking into account the role of translators in world civilization, the role of the peoples of the world in the development of culture, literature, art, science and technology in general. Formed as a science by the middle of the 20th century, the type of activity that includes translation theory and practice, or translation studies, plays an important role in modern linguistics. The work of our linguists, who have conducted research on the theory of translation and its teaching methods, is commendable.
Keywords: methodology, translation skills, foreign language teaching, translator competence, skills, professionalism.